Isolation and Characterization of Two Coumarin Compounds from the Chloroform Fraction of Scadoxus multiflorus (Martyn) Raf. (Amaryllidaceae) - Olaiya Akeem Ayodele; Tijani Tawakaltu Omolara; Abdullahi Sakynah Musa; Sule Mohammed Ibrahim (Chemistry Proceedings)
In this study, the aerial parts of Scadoxus multiflorus were extracted using methanol through a maceration process. The resulting methanol crude extract was subsequently partitioned with solvents including n-hexane, chloroform, ethyl acetate, and n-butanol. Extensive column chromatography separation of the chloroform fraction, followed by isocratic elution of two pooled fractions, led to the isolation of two coumarin derivatives: 2-methyl-2H-chromen-7-ol and 7-methoxy-2H-chromen-2-one. These compounds underwent various physicochemical analyses, such as chemical tests, melting point determination, and solubility assessments. Structural elucidation of the isolated compounds was conducted using UV spectroscopy, FT-IR, and 1D/2D NMR techniques. The final molecular structures were confirmed and named using ChemDraw.